Hypertension in the Elderly (Rhythmos, 2012)
In our aging society, most of the elderly aged >65 years are affected by systolic hypertension (HTN) [blood pressure (BP) >140 mmHg], which constitutes a major risk factor for organ damage and cardiovascular (CV) events. Management of HTN in the elderly represents a therapeutic dilemma because HTN trials had upper age limits or did not present age-specific results. However, the HYVET trial documented that therapy is beneficial even in those >80 years. In the elderly, systolic BP and pulse pressure emerge as potent risk factors for CV events. In the past an empiric formula "100+age" was used to estimate appropriate systolic BP. Diastolic BP is more important in younger people
Keywords: hypertension; elderly; antihypertensive drugs; secondary hypertension